+0  
 
0
40
2
avatar+10 

Solve for \(x\)\(\frac{3x - 1}{4x-4} = \frac23.\)

 

Should I simplify it, or...?

 

(I'm a new user so I don't know if I'm doing this correctly)

 May 2, 2022
edited by ChocoSwirl  May 2, 2022
 #1
avatar+2401 
0

Welcome ChocoSwirl.

 

(3x-1)/(4x-4) = 2/3

The first thing I want to do is to get rid of the denominator, I can do this my multiplying 3(4x-4) on both sides. Note than x can't be 1 since 4(1) - 4 = 0, and zero can't be a denominator. 

(3x-1)3 = 2(4x - 4)

Next, I'm going to expand. 

9x - 3 = 8x - 8

Going to subtract 8x from both sides. 

x - 3 = -8

And finally, I'm going to add 3 to both sides.

x = -5

 

I hope that made sense. :))

 

=^._>^=

 May 2, 2022
 #2
avatar+10 
+1

Wow thank you so much! :)

ChocoSwirl  May 2, 2022

7 Online Users

avatar